DEVELOPMENT OF INSTRUCTIONAL MATERIALS BASED LOCAL WISDOM IN SOCIAL STUDIES - FITRIYANTI FITRIYANTI; EMIL L. FAISAL; SANI SAFITRI; ERIAWATY ERIAWATY (Sriwijaya University Learning and Education International Conference, 2016)
This research is the development of research that aims to develop instructional materials based on local wisdom social studies valid and practical and has a potential effect on students understanding on the values contained in the local culture. This study uses a model of development Borg and Gall consisted of three phases: a preliminary study, product development, and product trials. Gathering data using questionnaires, tests, documentation and data analysis using quantitative descriptive. Expert review of assessment results show the value of 83.3% (valid) for expert material and 82.5% (valid) for the media expert. In the test phase one to one and small group of learners obtained responses were very good (82.5%) showed the practicality of the use of teaching materials. In the field evaluation trials in Palembang obtained the pretest and posttest at 3.62 at 6.07 which shows an increase of 2.35 with N-Gain value of 0.4 with the medium category. While at Palangkaraya also an increase of 1.28 with N-Gain value of 0.3 with the medium category. The research results obtained by the product of teaching materials based on local wisdom valid, practical, effective learners with a positive response by 82.5% (excellent) on the use of teaching materials based on local wisdom in social studies.